Global, regional, and national burdens of intraocular foreign bodies in children and adolescents from 1990 to 2019: a trend analysis - Hang Ren; Bo Jiang; Gaoqin Liu; Peirong Lu (BMC, 2023)
Abstract Background This study aimed to evaluate trends in global, regional, and national burdens of intraocular foreign bodies among children and adolescents (aged 0 − 19 years) between 1990 and 2019 according to age, sex, and socio-demographic index. Methods This study obtained data from the Global Burden of Disease Study 2019 and evaluated the number of cases, rates per 100,000 persons, and average annual percentage changes among children and adolescents. The annual percentage changes in the incidence and years lived with disability rates across various age groups were investigated using joinpoint software. Results For intraocular foreign bodies in children and adolescents, the incidence and year lived with disability rates decreased in all age groups between 1990 and 2019. However, the number of incident cases and years lived with disability increased from 1091.94 [95% uncertainty interval (UI), 610.91-1839.52] and 89,245 (95% UI, 6.65-18.67) in 1990 to 1134.85 (95% UI, 665.01-1867.50) and 92,108 (95% UI, 32,052-192,153) in 2019, respectively. Age was positively correlated with the number of cases, incidence, and years lived with disability rates. However, there were significant decreases in both the incidence and years lived with disability rates among children and adolescents, especially in the 15-18 years age group, males, and most high-income regions. Notably, the incidence and years lived with disability rates were significantly decreased in middle and high-middle socio-demographic index regions but were increased in low and low-middle socio-demographic index regions. Conclusions Despite the remarkable progress between 1990 and 2019 in reducing the global burden of intraocular foreign bodies, there has been an increase in the number of cases, with substantial disparity across age groups, sexes, regions, and countries. Our results could inform more effective strategies for reducing the burden among children and adolescents.